2003
DOI: 10.1021/bi0353777
|View full text |Cite
|
Sign up to set email alerts
|

Signal Recognition Particle Alu Domain Occupies a Defined Site at the Ribosomal Subunit Interface upon Signal Sequence Recognition

Abstract: The eukaryotic signal recognition particle (SRP) is essential for cotranslational targeting of proteins to the endoplasmic reticulum (ER). The SRP Alu domain is specifically required for delaying nascent chain elongation upon signal sequence recognition by SRP and was therefore proposed to interact directly with ribosomes. Using protein cross-linking, we provide experimental evidence that the Alu binding protein SRP14 is in close physical proximity of several ribosomal proteins in functional complexes. Crossli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…Fragile X Mental Retardation Protein (FMRP) was detected using the monoclonal antibody 1C3 (30). Affinity-purified anti-human SRP14, anti-human SRP19, anti-human SRP72 and anti-S15 antibodies were described before (7,28,31). Anti-human SRP9 antibodies were raised in chicken and affinity-purified.…”
Section: Methodsmentioning
confidence: 99%
“…Fragile X Mental Retardation Protein (FMRP) was detected using the monoclonal antibody 1C3 (30). Affinity-purified anti-human SRP14, anti-human SRP19, anti-human SRP72 and anti-S15 antibodies were described before (7,28,31). Anti-human SRP9 antibodies were raised in chicken and affinity-purified.…”
Section: Methodsmentioning
confidence: 99%
“…Purification of the proteins was described earlier (Huck et al 2004;Terzi et al 2004). All proteins were stored in 20 mM HEPES (pH 7.5), 500 mM KOAc (pH 7.5), 0.1 mM EDTA (pH 7.5), 0.01% NIKKOL, 10 mM DTT, and 10% glycerol.…”
Section: Protein Synthesis and Purificationmentioning
confidence: 99%
“…Cross-linking and cryo-electron microscopic (EM) studies have identified multiple contact sites between these targeting/translocation components and the ribosome. SRP makes six contacts with the ribosome: four located around the ribosomal exit site and two at the subunit interface (Pool et al, 2002;Halic et al, 2004;Terzi et al, 2004), which represent the sites involved in signal sequence recognition and elongation arrest, respectively. The Sec61p complex interacts with the ribosome at between four and six contact points, again located at the ribosomal exit site (Beckmann et al, 2001;Menetret et al, 2005).…”
Section: Introductionmentioning
confidence: 99%